'Therapeutic stoppage' creates a space where a 'moment of movement' will come. (2nd January 2017) - Morotomi, Yoshihiko
ABSTRACT: In this paper, the following points will be touched upon: 1. The ​​​​meaning of 'therapist thinking at the edge' (TAE) in the process of learning and growing as a person-centered and experiential​​​​ psychotherapist. 2. The meaning of Therapeutic Stoppage and the experience of 'Moment of Movement' (Rogers, 1956) and 'Vacuum' (Tomoda, 1962). I think that one of the most important and meaningful issues in person-centered and experiential psychotherapy in Japan during these 10 years is the development of the method 'Therapist TAE'. TAE is a thinking method for concept formation and theory construction by Gene Gendlin and Mary Hendricks (2004). 'Thinking at the edge' is a systematic way to articulate in new terms something which needs to be said but is at first only an inchoate 'bodily sense' (Gendlin, 2004). TAE is a systematic method on explication of implicit understanding (IU). TAE steps provide 14 forms: these are effective and orderly reference to IU. In Japan, TAE is applied to the method of reflection about clinical cases by the therapist and the method of theory building by​​​​ experienced middle-aged person-centered and experiential psychotherapists. This method is named 'Therapist TAE'.​​​​